2020
DOI: 10.1021/acs.jafc.0c02042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Harvest Date and Postharvest Treatment on Carotenoid and Flavonoid Composition in French Marigold Flowers

Abstract: The aim of this study was to characterize carotenoids and flavonoids present in French marigold flowers (Tagetes patula "Durango Red") as well as to assess the effects of harvest dates and postharvest treatments on these compounds. Carotenoids and flavonoids were quantified using their respective standards or semiquantified using relevant related standards. Lutein and its derivatives largely dominated the flower carotenoids, while the flavonoids were diverse with patuletin leading the list. Of the different po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Although genus Tagetes is known for species with proven industrial potential, the majority of previous studies focusing on chemical characterization of different extracts commonly revealed a smaller number of compounds with an incomplete picture of phytochemical diversity responsible for demonstrated biological activities. In the work of Bhave et al [ 51 ], French marigold flowers extracted in acidified MeOH, and characterized by HPLC-MS/MSC, revealed a total of 12 flavonoids identified from 26 peak compounds. Politi et al [ 52 ] used the same method and identified kaempferol and patuletin, along with 10 glycosylated flavonoids in the ethanolic extract of aerial parts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although genus Tagetes is known for species with proven industrial potential, the majority of previous studies focusing on chemical characterization of different extracts commonly revealed a smaller number of compounds with an incomplete picture of phytochemical diversity responsible for demonstrated biological activities. In the work of Bhave et al [ 51 ], French marigold flowers extracted in acidified MeOH, and characterized by HPLC-MS/MSC, revealed a total of 12 flavonoids identified from 26 peak compounds. Politi et al [ 52 ] used the same method and identified kaempferol and patuletin, along with 10 glycosylated flavonoids in the ethanolic extract of aerial parts.…”
Section: Discussionmentioning
confidence: 99%
“…Ten polyphenols were identified using analytical standards, while the identification of other components (in the absence of standards) was carried out according to their monoisotopic mass (obtained by full scan (FS) analysis) and MS n fragmentation, and confirmed by the literature data of metabolites identified in various Tagetes species [ 51 , 55 , 82 , 83 , 84 ]. RStudio software (version 1.3.1093) was used for the MS data evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…Some important chemical agents are found in the marigold extract, such as phenylpropanoids, carotenoids, flavonoids, thiophenes, quercetagetin, 6-hydroxykaempferol, quercetin, patuletin, quercetagetin-7-Oglucoside and others (Bhave et al 2020;Ratananikom et al 2021;Devrnja et al 2022). The compound produced by plants could vary depending on some factors: part of plant extracted, harvesting seasons, plant development stage, and geographical conditions (Salehi et al 2018).…”
Section: Phytochemical Compoundsmentioning
confidence: 99%
“…In a report by Siriamornpun et al [22], lutein content in Tagetes erecta L. flowers treated with HAD at 60 • C for 4 h decreased by over 50% compared to that in FD. In another study, the conversion of high molecular glycosyl flavonoids in Tagetes patula flowers into aglycones or intermediate flavonoid glycosides through the drying process was reported [23]. From these results, the effects of thermal drying on the chemical properties of marigold flowers, particularly in different cultivars, highlight the need for investigation.…”
Section: Introductionmentioning
confidence: 98%